COMPARATIVE EVALUATION OF DIFFERENT CARRIERS TO ENHANCE SOLUBILITY AND DISSOLUTION OF POOR WATER SOLUBLE DRUG - DHARA B. PATEL (International Journal of Pharma and Bio Sciences, 2014)
The aim of this study was to investigate the effect of different carriers on solubility and in vitro dissolution of poorly water soluble drug meloxicam (MLX). Solid dispersions with Polyethylene glycol-6000 (PEG6000), Poloxamer 188 (Plx188), Poloxamer 407 (Plx407) and inclusion complexes (ICs) with β cyclodextrin (β-CD) were prepared by different methods in three different weight ratios. All SDs and ICs were evaluated for percentage practical yield, drug content, solubility and dissolution studies and characterized by FTIR and powder X-ray diffraction studies. The improvement of solubility using polymers was in the following order: Plx188 > Plx407 > PEG6000 > β-CD. In Dissolution studies, maximum drug release (99.46% at 90 min) were obtained in 1:3 ratios of MLX to Plx188. Solid dispersion of MLX with Plx188 by fusion method in 1:3 ratios can be used to formulate fast dissolving solid dosage form to enhance drug dissolution.